KMCanvas: materialization of knowledge management (Advances in Knowledge Representation, 2022)
It has always been an aspiration to have a structure to drive the integration of knowledge, the alignment of knowledge demands with business and IT, under the influence of information science, agile project management and business process management. KMCanvas was then conceived and created to pave the way to positive results and the assertive implementation of information management and knowledge management in public or private organizations. The question raised was: how can the implementation of knowledge management in organizations make use of a Canvas? The methodological contribution came from Design Science Research, a method that guides the construction of artifacts with rigor and relevance, and from Design Science, an appropriate paradigm to carry on scientific research in information, technology, engineering and management. Eleven specialists were chosen for KMCanvas validation. As a result, we present KMCanvas, a Canvas for KM implementation as an innovative choice for organizations.